DIPLOMASI DAN POWER: SEBUAH KAJIAN ANALISIS - Rendi Prayuda (UIR Press, 2019)
After the 1961 of Wina convention, diplomacy became one of the containers for the actualization of relations between countries in the international political arena to convey the national interests of a country to other countries. The national interest of a country is certainly a diplomatic mission for the state in the scope of international practice. The practice of a country's diplomacy success is of course influenced by various factors and the power factor is one of the determining factors for a country's diplomatic success. This paper use a descriptive qualitative approach with the collect data by library research. The results of this study indicate that the effectiveness of a country's diplomacy depends on the extent of its own national strength. Some things that determine the success of diplomacy can be analyzed from the diplomatic environment in the form of the international system, the diplomatic environment and domestic relations. While the concept of power is determined by elements that do not change (natural resources, geography, demographics and population) as well as elements that are easily changed (character and morality of the nation, the quality of government and diplomatic quality).